Slack, Slick, and Sodium-Activated Potassium Channels - Leonard K. Kaczmarek (2013)
The Slack and Slick genes encode potassium channels that are very widely expressed in the central nervous system. These channels are activated by elevations in intracellular sodium, such as those that occur during trains of one or more action potentials, or following activation of nonselective cationic neurotransmitter receptors such as AMPA receptors. This review covers the cellular and molecular properties of Slack and Slick channels and compares them with findings on the properties of sodium-activated potassium currents (termed K Na currents) in native neurons. Human mutations in Slack channels produce extremely severe defects in learning and development, suggesting that K Na channels play a central role in neuronal plasticity and intellectual function.